2010
DOI: 10.1128/jvi.00894-10
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of Kaposi's Sarcoma-Associated Herpesvirus Reactivation with Epstein-Barr Virus Latency and Cellular Growth Mediated by the Notch Signaling Pathway in Coinfected Cells

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) is the etiologic agent of primary effusion lymphoma (PEL).Kaposi's sarcoma-associated herpesvirus (KSHV) is the etiologic agent of Kaposi's sarcoma (KS) and primary effusion lymphoma (PEL). PEL is a body cavity based lymphoma that is rapidly fatal (15,24,37,56,63). Multiple, continuous PEL cell lines were established by culturing clinical samples from PEL patients (13,54,60). These cell lines were the first tissue culture models for KSHV infection (53,60). Approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 69 publications
0
26
0
Order By: Relevance
“…Our previous work demonstrated that RTA activates LANA expression during the early stages of infection by recruiting RBP-J bound to its cognate sequence within LANA promoter (39). Other groups have also shown that RTA transactivates the Epstein-Barr virus (EBV) latent membrane protein 1 (LMP-1) and latency C promoters (Cp) in uninfected cells and in dually infected PEL cells by forming a complex with RBP-J and its cognate sequence within the promoters (75). Therefore, we postulated that disruption of RBP-J binding to the LANA promoter will have a profound effect on switching of the virus from latent to the lytic replication.…”
mentioning
confidence: 99%
“…Our previous work demonstrated that RTA activates LANA expression during the early stages of infection by recruiting RBP-J bound to its cognate sequence within LANA promoter (39). Other groups have also shown that RTA transactivates the Epstein-Barr virus (EBV) latent membrane protein 1 (LMP-1) and latency C promoters (Cp) in uninfected cells and in dually infected PEL cells by forming a complex with RBP-J and its cognate sequence within the promoters (75). Therefore, we postulated that disruption of RBP-J binding to the LANA promoter will have a profound effect on switching of the virus from latent to the lytic replication.…”
mentioning
confidence: 99%
“…Since ectopic RTA expression in mouse cells has earlier been shown to function in the activation of transfected reporter genes (13,14,23), we wondered if the defects observed might have to do with the nature of the chromatinized DNA template. Accordingly, we asked if lytic reactivation would be more efficient if induction was triggered by exposure to histone deacetylase (HDAc) inhibitors like valproic acid or sodium butyrate (N-butyrate).…”
mentioning
confidence: 99%
“…In the present study, the PI3K/Akt signaling pathway was shown to be involved in the induction of survivin expression by LMP-1. Although the Notch and MAPK pathways are activated by LMP-1 in other diseases (30,31), we found that the roles of the Notch and MAPK pathways in NKTL were not obvious. Thus, we can infer that LMP-1 induced survivin expression by activating the NF-κB and PI3K/Akt pathways in NKTL.…”
Section: Discussionmentioning
confidence: 66%